Survival effect of pre-RT PET-CT on cervical cancer: Image-guided intensity-modulated radiation therapy era - Su, Chih-Hsiung; Chen, Wan-Ming; Chen, Mingchih; Shia, Ben-Chang; Wu, Szu-Yuan (Frontiers in Oncology, 2023)
Purpose: No large-scale, well-designed randomized study with a long-term follow-up has evaluated the survival effect of pretreatment 18-fluorodeoxyglucose positron emission tomography–computed tomography (18FDG-PET–CT) on patients with stage IB–IVA cervical cancer receiving image-guided intensity-modulated radiation therapy (IG-IMRT). Therefore, in this propensity score–matched, population-based cohort study, we investigated these survival effects. Patients and Methods: We included 4167 patients with stage IB–IVA cervical cancer receiving radiotherapy (RT) or concurrent chemoradiotherapy (CCRT) through the IG-IMRT technique. The patients were categorized into two 1:2 propensity score–matched groups depending on whether they underwent pretreatment 18FDG-PET–CT, and their outcomes were compared. Results: We included 2778 and 1389 patients with cervical cancer in the nonpretreatment and pretreatment PET–CT groups, respectively. Univariable and multivariable analyses revealed an association between pretreatment PET–CT and improved survival in the patients (in the adjusted model, the adjusted hazard ratio [aHR] was 0.88; 95% confidence interval [CI], 0.80–0.97: P = 0.010). Regardless of the cancer stage (early or advanced), pretreatment PET–CT was significantly superior to nonpretreatment PET–CT in terms of all-cause death (aHR, 0.78; 95% CI, 0.60–0.92; P = 0.013 and aHR, 0.90; 95% CI, 0.81–0.99; P = 0.039 for the early [IB–IIA] and advanced stages [IIB–IVA], respectively). Conclusions: Pretreatment 18FDG-PET–CT might be associated with longer survival in patients with stage IB–IVA cervical cancer receiving RT or CCRT, especially in the era of IG-IMRT.